Organ distribution of 4-MEC, MDPV, methoxetamine and α-PVP: comparison of QuEChERS and SPE - Lehmann, Sabrina; Schulze, Bastian; Thomas, Andreas; Kamphausen, Thomas; Thevis, Mario; Rothschild, Markus A.; Mercer-Chalmers-Bender, Katja (Forensic Toxicology, 2018)
Purpose: An organ distribution investigation was carried out on two deceased (A and B) who consumed 4-methylethcathinone (4-MEC), methylenedioxypyrovalerone (MDPV), methoxetamine (MXE) and α-pyrrolidinopentiophenone (α-PVP). Methods: The detection of the aforementioned drugs in the specimens was performed on a liquid chromatography–tandem mass spectrometry system. Two different extraction methods were compared with each other—a quick, easy, cheap, effective, rugged and safe (QuEChERS) approach and an automated Instrument Top Sample Preparation-solid phase extraction (ITSP-SPE). Standard addition method was used to quantify the drugs. Results: 4-MEC, MDPV and MXE were detected in all collected tissues and body fluids of the two deceased. α-PVP was also detectable in deceased A. Deceased A showed femoral blood concentrations of 97 µg/L 4-MEC, 396 µg/L MDPV, 295 µg/L MXE and 4 µg/L α-PVP measured after extraction by QuEChERS and 118 µg/L 4-MEC, 342 µg/L MDPV, 385 µg/L MXE and 4 µg/L α-PVP measured after ITSP-SPE. Deceased B revealed heart blood concentrations of 8 µg/L 4-MEC, 3 µg/L MDPV and 2 µg/L MXE after extraction by QuEChERS and 8 µg/L 4-MEC and 1 µg/L MXE after ITSP-SPE. Conclusions: Both preparation techniques were suitable for quantifying NPS in organ tissues and body fluids. With respect to the autopsy findings, the cause of death of deceased A was determined to be an acute intoxication with NPS. No certain cause of death could be ascertained for deceased B.
CRIS-Team Scopus Importer:2025-02-28
Keywords: 4-MEC; ITSP-SPE; LC–MS/MS; New psychoactive substances; Organ distribution; QuEChERS